Low-temperature plasma magnetron discharge - I. Sh. Nevliudov; D. V. Gurin; V. N. Gurin; K. L. Khrustalev (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
The article investigates a low-temperature plasma of the magnetron discharge of a device used for the synthesis of dielectric films by reactive cathode sputtering. The aim of the study is to determine the temperature characteristics of plasma particles and a sputtered substance, as well as the mechanism for the formation of a chemical bond between sputtered atoms and active gas molecules. A study of the composition and energy parameters of the plasma, as well as the chemical composition of the particles obtained by sputtering, was carried out by a spectroscopic method. The quantitative composition was determined by a mass spectrometer to determine the composition of the sputtered particles.